Photocatalytic degradation of Rhodamine B dye by nanostructured powder systems containing nanoencapsulated curcumin or ascorbic acid and ascorbyl palmitate liposomal - Gundel S.S. (2023)
© 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.Due to inadequate treatment and incorrect management, wastewater with dyes has a great toxic potential as an environmental liability, representing a major concern. In this context, this work aims to investigate the potential application of nanostructured powdery systems (nanocapsules and liposomes) in the photodegradation of Rhodamine B (RhB) dye, under UV and visible irradiation. Curcumin nanocapsules and liposomes containing ascorbic acid and ascorbyl palmitate were prepared, characterized, and dried using the spray drying technique. The drying processes of the nanocapsule and the liposome showed yields of 88% and 62%, respectively, and, after aqueous resuspension of the dry powders, it was possible to recover the nanocapsule size (140 nm) and liposome size (160 nm). The dry powders were characterized by Fourier transform infrared spectroscopy (FTIR), N2 physisorption at 77 K, X-ray diffraction (XRD), and diffuse reflectance spectroscopy (DRS-UV). Under UV irradiation, 64.8% and 58.48% of RhB were removed with nanocapsules and liposomes, respectively. While under visible radiation, nanocapsules and liposomes were able to degrade 59.54% and 48.79% of RhB, respectively. Under the same conditions, commercial TiO2 showed degradation of 50.02% (UV) and 42.14% (visible). After 5 cycles of reuse, there was a decrease of about 5% for dry powders under UV irradiation and 7.5% under visible irradiation. Therefore, the nanostructured systems developed have potential application in heterogeneous photocatalysis for the degradation of organic pollutants, such as RhB, as they demonstrated superior photocatalytic performance to commercial catalysts (nanoencapsulated curcumin > ascorbic acid and ascorbyl palmitate liposomal > TiO2).